Proceedings of the 2013 Conference on Computer Supported Cooperative Work 2013
DOI: 10.1145/2441776.2441855
|View full text |Cite
|
Sign up to set email alerts
|

Complementarity of input devices to achieve knowledge sharing in meetings

Abstract: In co-located meetings, participants create and share content to establish a common understanding. In this paper, we present a collaborative environment that enables group members to create and share content simultaneously by providing them with different kinds of individual input devices and a shared workspace. We also report on an exploratory study to investigate the influence of the input device used on the shared knowledge produced by the group. The results suggest that driven by the affordances, various i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…Olson et al [42] also studied collaborative writing within student teams at undergraduate levels with Google Docs, and found variability in collaborative writing strategies ranging from synchronous to asynchronous. Moreover, they also observed the inherent dynamism in acquisition and transfer of roles during writing and editing activities, and found that balanced participation and exhibited leadership in student teams resulted in high-quality writing (similar observations in collocated student teams were also reported by [55,56]). Awareness tools that visualize individual contributions, document change history, and overall collaboration synthesis have also been developed and evaluated in the context of collaborative writing with Google Docs [57].…”
Section: Technological Support For Co-writing Activitiessupporting
confidence: 65%
“…Olson et al [42] also studied collaborative writing within student teams at undergraduate levels with Google Docs, and found variability in collaborative writing strategies ranging from synchronous to asynchronous. Moreover, they also observed the inherent dynamism in acquisition and transfer of roles during writing and editing activities, and found that balanced participation and exhibited leadership in student teams resulted in high-quality writing (similar observations in collocated student teams were also reported by [55,56]). Awareness tools that visualize individual contributions, document change history, and overall collaboration synthesis have also been developed and evaluated in the context of collaborative writing with Google Docs [57].…”
Section: Technological Support For Co-writing Activitiessupporting
confidence: 65%
“…Despite all the aforementioned affordances, and considering all the multi-task desirable properties, the majority of the currently available shareable interface systems created for research purposes, consist of a single program that already includes all the necessary facilities to cover every subtask of the main activity. This is, however, consistent with the purpose of most research, because, in a collaboration co-located setting, CSCW researchers typically focus their investigations on the human factors in multi-user interaction, such as how input devices can be more effectively distributed between users in order to optimize group dynamics (Kim and Snow 2013;Verma et al 2013), or on studying different strategies to access digital and physical items from the perspective of digital content sharing (Verma et al 2013), control sharing (Jordà et al 2010;Kim and Snow 2013), or proxemics (Ballendat et al 2010).…”
Section: Multi-tasking In Shareable Interfaces: Current Situation Andmentioning
confidence: 77%
“…Thus, to measure meeting effectiveness, we primarily quantified three indicators: task efficiency, goal attainment, and perception of achieving the meeting goal. Task efficiency denoted the time teams spent to complete meeting tasks (Verma et al, 2013). The second aspect was objectively measured as the degree to which users accomplish specific goals (Prenner, Klünder, & Schneider, 2018).…”
Section: Research Questionsmentioning
confidence: 99%